TINDAK PIDANA PELECEHAN SEKSUAL YANG TERJADI DI TRANSPORTASI UMUM BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL - Siahaan, Sahala MPH; Sumanto, Listyowati (Ensiklopedia Education Review, 2024)
Abstract: Sexual harassment often occurs in open spaces and public places, it turns out that sexual harassment also often occurs in public transportation. Therefore, safety and comfort in public transportation must be improved, because many people use public transportation for work, school, and others. This study uses a normative legal research type and is descriptive. Secondary data is analyzed qualitatively. Concluding uses deductive logic. Law no. 12 of 2022 concerning Criminal Acts of Sexual Violence, as a provision to prevent criminal acts of sexual violence. Prevention of sexual harassment must be carried out by both the public who use public transportation services, public transportation service providers, and the government in this case the Indonesian National Police, so that sexual harassment does not occur against women in public transportation. Protection, especially for women as users of public transportation, must be a priority, to provide a sense of security and comfort for users of public transportation services, so that in the future sexual harassment will not occur again in public transportation.Keywords: Sexual Harrasment, Public Transportation, Criminal Offense.